Pengaruh Penerapan Proyek Ekonomi Kreatif Berbasis SCAMPER untuk Meningkatkan Kreativitas Siswa SD pada Pembelajaran IPAS - Cahyaning, Alin; Ariyani, Yusinta Dwi (Indonesian Journal of Elementary Education and Teaching Innovation, 2025)
The low level of student creativity can be influenced by teaching methods that are inappropriate and not aligned with the needs of the students. This study aims to understand the implementation, impact, and responses of teachers and students to the application of SCAMPER-based creative economy projects to enhance student creativity in IPAS learning. This study uses a quantitative approach with a quasi-experimental method employing the Nonequivalent Control Group Design – Posttest Only. The inferential statistical analysis used is the t-test with a significance level of 0.05. The population and sample in this study are 52 fifth-grade students from SD Negeri 1 Sumberagung. Each experimental group and control group consists of 26 students determined by the saturated sampling technique. The instruments used in this study are observation sheets for the implementation of learning, product assessment with CPSS, and questionnaires for teachers and students. The results of this study indicate that 1) the implementation of the SCAMPER-based creative economy project was carried out well based on the results of the learning implementation observation sheet. 2) based on the assessment of students' creative products using CPSS and the results of the t-test analysis with a result of 0.026 < 0.05, the hypothesis is accepted, stating "there is an influence of implementing the SCAMPER-based creative economy project to enhance the creativity of elementary school students in IPAS learning." 3) The response or perception of teachers and students towards the implementation of the SCAMPER-based creative economy project received very good feedback based on the results of the teacher and student questionnaires. Thus, it can be concluded that there is a significant difference in the level of creativity between the experimental class students who applied the SCAMPER method and the control class students who did not apply the SCAMPER method.Keyword: Project Learning, SCAMPER, Creativity